Effect of Rearing in Small-Cell Combs on Activities of Catalase and Superoxide Dismutase and Total Antioxidant Capacity in the Hemolymph of Apis mellifera Workers - Piotr Dziechciarz; Aneta Strachecka; Grzegorz Borsuk; Krzysztof Olszewski (MDPI AG, 2023)
Honeybee nests constructed without man-made wax foundation have significantly more variability of cell widths/sizes than those in commercially-kept colonies. The effects of this natural variability in comb cell widths on individual and colony traits have not been explained to date. The investigation of this problem can lead to new findings about the biology, physiology, and possibly, the evolution of the honeybee. The aim of the study was to compare the catalase and superoxide dismutase activities and the total antioxidant capacity levels in the hemolymph of honeybee workers reared in small-cell combs and standard-cell combs in colonies kept simultaneously on standard- and small-cell combs. The ratio of the small-cell combs to the standard-cell combs in the nest was 1:1. The workers reared in small-cell combs were characterized by higher antioxidant activities in the hemolymph than those reared in standard-cell combs. Consequently, their hemolymph had a greater antioxidant capacity, which indicates that they may be better predisposed to be foragers than workers reared in standard-cell combs. To describe the physiological differences between worker bees reared in small- and standard-cell combs in the same colony, the role of the considerable variation in the cell width in natural combs built without the use of artificially produced wax foundation is worth elucidating. The comparison of the apiary and cage experiments indicated that changes in antioxidant activities predominantly result from worker activities, especially those requiring the intensification of metabolism, rather than the age of the worker bees. To reduce the impact on the results of random environmental factors potentially present in one-season studies of honeybee research, investigations should preferably be carried out over a few consecutive years.